Peningkatan Hasil Belajar IPA Menggunakan Model Cooperative Learning Tipe Student Teams Achievment Division (STAD) - Sri Yanti (Jurnal LENTERA: Jurnal Studi Pendidikan, 2022)
This study aims to determine the extent to which science learning outcomes have been improved by using a cooperative learning model of the student teams achievement division (STAD) type in class VIII students of SMP Negeri 5 Taliwang. The type of research used is classroom action research, the CAR procedure consists of 2 cycles or more. Each cycle is carried out in accordance with the changes to be achieved. Each cycle consists of 1) planning, 2) implementing actions, 3) observing, 4) reflecting. This research was conducted on eighth-grade students at SMP Negeri 5 Taliwang. From the results of the study, it was found that student learning outcomes in light science learning using the STAD type cooperative learning model in class VIII SMP Negeri 5 Taliwang experienced an increase in each cycle, this can be seen from the level of student learning mastery per cycle, namely in the pre-cycle with a KKM of 75 students. In the pre-cycle there were 8 students or 33.33% who completed, then there was an increase in the first cycle, namely, there were 13 students or 54.17% and in the second cycle there were 20 students or 83.33%, while the learning activities of students in the first cycle were 11 students or 45.83% and in the second cycle there were 21 students or 87.50%, the results were in accordance with the specified indicators.